2009
DOI: 10.1521/psyc.2009.72.2.177
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Attitudes Among Black Americans Towards Psychiatric Genetic Research

Abstract: With increasing emphasis on understanding genetic contribution to disease, inclusion of all racial and ethnic groups in molecular genetic research is necessary to ensure parity in distribution of research benefits. Blacks are underrepresented in large-scale genetic studies of psychiatric disorders. In an effort to understand the reasons for the underrepresentation, this study explored black participants’ attitudes towards genetic research of psychiatric disorders. Twenty-six adults, the majority of whom were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 40 publications
1
59
1
Order By: Relevance
“…Consistent with prior studies, principal concerns of SDMs were that a genetic sample might be diverted for inappropriate purposes, or would lead to insurance and employment discrimination. 14,18,23,27 However, in contrast to these previous investigations, was our finding that SDMs perceived the risk associated with gene variation research largely as the risk associated with acquiring the genetic sample (i.e., whether or not sample acquisition involved an invasive procedure), as opposed to characteristics of the sample itself. This altered frame of reference might reflect the acuteness of the illness of their loved ones, as well as the number and nature of medical interventions these individuals had recently undergone.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Consistent with prior studies, principal concerns of SDMs were that a genetic sample might be diverted for inappropriate purposes, or would lead to insurance and employment discrimination. 14,18,23,27 However, in contrast to these previous investigations, was our finding that SDMs perceived the risk associated with gene variation research largely as the risk associated with acquiring the genetic sample (i.e., whether or not sample acquisition involved an invasive procedure), as opposed to characteristics of the sample itself. This altered frame of reference might reflect the acuteness of the illness of their loved ones, as well as the number and nature of medical interventions these individuals had recently undergone.…”
Section: Discussioncontrasting
confidence: 97%
“…Accordingly, focus groups (FGs) were conducted in conference rooms adjoining the ICUs while the loved ones of SDMs received treatment for their critical illness. FG study guides were developed on the basis of themes related to gene variation research, including general familiarity with genetic data, 23 features that might render genetic data distinct from nongenetic data, 13 concerns about misuse, 12,23 confidentiality, 18,23 and future use. 17 Hypothetical cases, vignettes, and samples of the institutional review board (IRB)-approved consent language were used to generate discussion.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this stance, our ongoing analysis of the subsection for perception of benefits in the QGR indicates more optimistic views among Black participants that BD genetic studies could lead to prevention of BD and to development of gene therapy. Murphy and Thompson [2009] however, found no support for altruism as an important factor for participation in psychiatric genetic studies among Blacks in their community sample with 72% mental illness history. Rather, they found that Blacks with less education, who are unwilling to participate in genetic studies, expressed more interest in participating only for financial incentives.…”
Section: Discussionmentioning
confidence: 89%
“…The resulting breast cancer genetic epidemiology study, "The Jewels in Our Genes study," was designed to search for novel genetic loci associated with breast cancer in African American pedigrees. Our study was the first of its kind; reasons for this include challenges of identification and access to appropriate families, failure to recruit adequate sample sizes, and failure of inclusion of this audience and these patients in the scientific discovery process (Johnson et al 2011;Murphy and Thompson 2009). …”
Section: Introductionmentioning
confidence: 99%